2011
DOI: 10.1186/cc10546
|View full text |Cite
|
Sign up to set email alerts
|

Identifying critically ill patients who benefit the most from nutrition therapy: the development and initial validation of a novel risk assessment tool

Abstract: IntroductionTo develop a scoring method for quantifying nutrition risk in the intensive care unit (ICU).MethodsA prospective, observational study of patients expected to stay > 24 hours. We collected data for key variables considered for inclusion in the score which included: age, baseline APACHE II, baseline SOFA score, number of comorbidities, days from hospital admission to ICU admission, Body Mass Index (BMI) < 20, estimated % oral intake in the week prior, weight loss in the last 3 months and serum interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
668
5
41

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 640 publications
(769 citation statements)
references
References 22 publications
25
668
5
41
Order By: Relevance
“…High nutritional risk was present in half of the sample. As described in the original study [14,18] in our work NUTRIC score was associated with the target clinical outcomes; it had low positive predictive value (32.7%) and high negative predictive value (88.8%) to predict 28-day mortality. In this study patients at high nutritional risk had higher LOS, fewer days free of MV and increased 28-day mortality.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…High nutritional risk was present in half of the sample. As described in the original study [14,18] in our work NUTRIC score was associated with the target clinical outcomes; it had low positive predictive value (32.7%) and high negative predictive value (88.8%) to predict 28-day mortality. In this study patients at high nutritional risk had higher LOS, fewer days free of MV and increased 28-day mortality.…”
Section: Discussionmentioning
confidence: 51%
“…The score was calculated with data from the first 24 h after ICU admission. The NUTRC score ranges from zero to nine; a score ≥5 indicates a high nutritional risk [14]. Main outcome was mortality from all causes at 28 days after admission to the ICU; LOS and days without invasive mechanical ventilation (days free of MV) were secondary outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CALORIES trial, in both groups, the amount of nutrition delivered was below target but similar to that seen in previous studies in which nutritional targets were also commonly not met. 67,73,74 This suggests that there are substantial practical and organisational obstacles for both routes of feeding. Other research, more recently, has suggested that it is adequacy of protein intake, rather than simply energy intake, which requires to be supported in critical illness.…”
Section: Results In Contextmentioning
confidence: 99%
“…The NUTRIC risk assessment score (19) and other tools (20) can possibly identify critically ill patients who benefit the most from the nutritional therapy. Unfortunately, the majority of critically ill patients experience harm because they do not receive adequate nutritional intake (21).…”
Section: Nutritional Risk In the Critically Ill Scorementioning
confidence: 99%